Perancangan Sistem Informasi Honor Mengajar Guru Di Sma Al Ma’soem - Muhamad Fahmi Nugraha; Indah Mardiyah Lestari (Jurnal ICT : Information Communication & Technology, 2020)
The payroll system is a function of human resource management. Its main role is to reward teachers in the form of salaries in exchange for contributions to schools and their performance.The purpose and purpose of this report is to minimize the risk of duplication and deletion of data, make it easier to present reports so that they can be generated automatically, make it easier for TU staff to calculate the teaching honorarium of teachers at SMA Al Ma'soem.The method used in system design is SDLC (System Development Life Cycle). Where in its application using the waterfall model, namely the Waterfall method is a sequential software development process, where progress is seen as continuing to flow downward (like a waterfall) through the phases of planning, modeling, implementation (construction), and testing. The system modeling uses Flow maps, Data Flow Diagrams, Structure Charts, Data Dictionary and ERD.Thus, the Information System for Teaching Honor Teachers at Al Ma'soem High School is expected to assist in processing data and processing teacher payrolls.